First-neighbor specificities of actinomycin-DNA bindings by circular dichroism. - Allen, F S (1977)
The circular dichroism spectra of eleven double-stranded DNAs, five natural with known nearest neighbor frequencies and six synthetic polydimers and polytrimers, were measured from 210 to 310 nm in the absence and presence of increasing amounts of actinomycin up to saturation. Based on the fact that the circular dichroism of nucleic acids is a nearest-neighbor frequency-dependent property, matrix analysis of the problem revealed which neighbor sets were perturbed by actinomycin, presumably by intercalation of the planar moiety of the molecule. The intercalation sites can be separated into three families. The first-neighbor units GpC and CpG are very favorable binding sites for actinomycin. ApG, CpC, ApC, TpC, and TpG appear to be less attractive sites, while ApT, TpA, and ApA are unfavorable sites.